2014
DOI: 10.1016/j.redox.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol fraction of extra virgin olive oil protects against endothelial dysfunction induced by high glucose and free fatty acids through modulation of nitric oxide and endothelin-1

Abstract: Epidemiological and clinical studies have reported that olive oil reduces the incidence of cardiovascular disease. However, the mechanisms involved in this beneficial effect have not been delineated. The endothelium plays an important role in blood pressure regulation through the release of potent vasodilator and vasoconstrictor agents such as nitric oxide (NO) and endothelin-1 (ET-1), respectively, events that are disrupted in type 2 diabetes. Extra virgin olive oil contains polyphenols, compounds that exert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 47 publications
2
85
0
1
Order By: Relevance
“…All of these events may be related to the effects of specific fatty acids, polyphenols, phytoestrogens or other minor components present in EVOO and/or nuts. In this way, Moreno-Luna et al [42] reported that olive oil polyphenols decrease BP in young women with mild hypertension and we also observed that olive oil polyphenols have a protective effect on the imbalance of NO/ET-1 induced by hyperglycemia and free fatty acids [43].…”
Section: Discussionsupporting
confidence: 76%
“…All of these events may be related to the effects of specific fatty acids, polyphenols, phytoestrogens or other minor components present in EVOO and/or nuts. In this way, Moreno-Luna et al [42] reported that olive oil polyphenols decrease BP in young women with mild hypertension and we also observed that olive oil polyphenols have a protective effect on the imbalance of NO/ET-1 induced by hyperglycemia and free fatty acids [43].…”
Section: Discussionsupporting
confidence: 76%
“…This table shows the reported dietary nutrients/drugs that have been shown to be effective against FFAs-induced ED, and the potential mechanisms highlighted in these studies. Two differently-colored texts in the table have been used to highlight different studies on the same drug or the use of more than one study model used within the same articleDrug/dietary constituentEffects/relevant mechanismsNature of the studyω-3 PUFAs (EPA)AMPK/eNOS pathway ↑In vitro study on primary HUVECs [18]iNOS ↓EC apoptosis, Caspase-3,p53/MAPK, Bax ↓NADPH oxidase/ROS ↓NF-κB activation ↓ Astragalus membranaceus NO ↑Ex vivo study on rat aortic rings [134, 141]Endothelium-dependentvasodilation ↑NF-κB ↓Cyanidin-3-O-glucosideOxidative stress ↓In vitro study on primary HUVECs [131]NF-κB activation and adhesionmolecules ↓Nrf2/EpRE pathway ↑Dihydropyridine calcium channel blockers (Nifedipine and amlodipine)Forearm blood flow responses toClinical trial [128]ACh ↑Leucocyte activation ↓Oxidative stress ↓In vitro monocytic cells [128]NF-κB ↓TNF-α, IL-6 ↓In vitro study on HUVECs [131]IKKβ/NF-κβ phosphorylation ↓IRS-1 phosphorylation ↓NO production ↑L-carnitineEndothelium-dependent leg blood flow ↑Clinical trial [107]LosartanVasodilation ↑Clinical study [139]eNOS activity ↑IRS-1 phosphorylation ↓Study on rats [139]Olive oil polyphenolseNOS activity ↑In vitro study on ECV304 cells [102]ET-1 ↓PerindoprilVasodilation ↑Clinical study [141]SalidrosideeNOS activation, NO production ↑In vivo study on HFD-fed ApoE −/− mice [106]AMPK/PI3K/Akt/eNOS pathway,Cellular AMP/ATP ratio ↑Atherosclerotic lesion ↓Withaferin AROS, TNF-α, IL-6 ↓In vitro stu...…”
Section: Role Of Ffas In Inducing Ed: Evidence From Clinical and Expementioning
confidence: 99%
“…Lopez-Villodres et al [84] found that HT supplementation (10 mg/kg/day × 2 months) increased in diabetic rats the levels of nitrites and nitrates, potent donors of NO acting as vasorelaxing agent. In addition, Storniolo et al [85] demonstrated that HT (10 µM) counteracted hyperglycemia-induced endothelin-1 expression, a well-known hypertensive agent, in a more extend than oleic acid.…”
Section: Hydroxytyrosol and Hypertensionmentioning
confidence: 99%
“…HT was reported to be ineffective on eNOS expression and activity (i.e., phosphorylation on its Ser1177) in absence of oxidative stress in HUVECs (0.1 to 100 µM) [134]. In an endothelial cell culture model of hyperglycemia, Storniolo et al [85] showed that HT (10 µM) increases NO • production, which is correlated to an increase of endothelial nitric oxide synthase phosphorylation (P-eNOS)/endothelial nitric oxide synthase (eNOS) ratio. When stimulated by acetylcholine, an activator of eNOS/NO • signaling pathway, HT increased NO • production, more than oleic acid; this increase was linked to higher intracellular calcium concentration.…”
Section: Associated Complications: Oxidative Stress Inflammationmentioning
confidence: 99%